Association between dynamic obesity and mortality in patients with first-ever ischemic stroke: A hospital-based prospective study. Issue 38 (18th September 2020) - Wang, Ju; Li, Jijie; Li, Mier; Hou, Lisha; Zhu, Ping; Du, Xudong; Zhou, Muke; Zhu, Cairong
Abstract : Abstract: Although obesity is an established risk factor of primary stroke, the association between obesity and post-stroke mortality remains unclear. The aim of this study was to investigate the association between dynamic obesity status and mortality in survivors of their first stroke in China. Of 775 patients with first-ever ischemic stroke included in a longitudinal study, 754 patients were included in this study and categorized into 4 categories of body mass index (BMI) (underweight, normal weight, overweight, and obese) and 2 categories of waist circumference (WC) (normal WC and abdominal obesity) according to standard Chinese criteria. The mortality information and obesity status were obtained via telephone follow-up every 3 months, beginning in 2010 through 2016. Time-dependent Cox proportional hazards models were used to estimate the unadjusted and adjusted hazard ratios (HRs) for the relationship between all-cause mortality and dynamic obesity status. Of 754 patients, 60.87% were male, and the overall mean age was 61.45 years. After adjusting for possible confounders, significant inverse associations were identified between BMI and WC and all-cause mortality. Compared with those with normal BMI or WC, those with abdominal obesity or overweight had a significantly lower risk of all-cause mortality (HR and 95% confidence intervals [CIs]: .521 [.303–.897] and 0.545 [.352–.845], respectively), whereas patients with underweight had the highest risk and those with obesity had lower risk of mortality, though it was not statistically significant (1.241 [.691–2.226] and .486 [.192–1.231], respectively). Overweight and abdominal obesity were paradoxically associated with reduced risk of mortality in patients who survived their first-ever ischemic stroke in China. Future prospective studies must look at evaluating the role of obesity in different stroke subtypes and devise appropriate weight-management strategies for optimal prognoses in secondary prevention in these survivors.